Implementating multiple representation-based worksheet to develop critical thinking skills - Abdurrahman, Abdurrahman; Setyamımgsıh, Cris Ayu; Jalmo, Tri (Journal of Turkish Science Education, 2024)
This study aimed to foster students' critical thinking skills through the use of multiple representationbased worksheet. Through a quasi-experimental research design (non-equivalent control group design), the sample of the study consisted of 74 students drawn from a junior high school in North Lampung. This sample was divided into two groups to assign the experimental and control groups. The experimental group was exposed to multiple representation-based worksheet, while the control group was instructed with conventional worksheet The results of independent samples t-test showed that the experimental group was effective in fostering critical thinking skills (N-Gain = 0,34 --medium category). Furthermore, the study found the following indicators: providing an elementary clarification (N-Gain = 0,51 --medium category), building basic support (N-Gain = 0,39 --medium category), inferring (N-Gain = 0,24 --low category), making advance clarification (N-Gain = 0,46 –medium category), and setting the strategies and tactics (N-Gain = 0,10 --low category).
Keywords: critical thinking skills; multiple representations; student worksheet